Literature review and Optimization of Process parameters for machining different materials with CNC - Kumar, Er. Kunthlesh (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
This paper discuss of literature review of different materials on CNC. Today CNC technology has major contribution in industries. CNC machines are main platform in the contribution of good quality products in industries [15]. Basically CNC machines are automated operating machines which are based on code letters, numbers and special characters. The numerical data required for manufacturing a part provided by machine is called CNC (Computer Numerical Controlled).